Evaluating resistance to infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) cells using CRISPR/Cas editing - Mantsopoulou, Marina (The University of Edinburgh, 2021)
Infectious Pancreatic Necrosis (IPN) is a highly transmissible viral disease which constitutes a major constraint in the production of cultured salmonid species worldwide, causing varying mortality rates and important economic losses in several countries. Previous studies focusing on the genetic basis of IPNV (Infectious Pancreatic Necrosis Virus) resistance in Atlantic salmon discovered a QTL of major effect, which has been exploited to improve resistance of Atlantic salmon stocks using marker-assisted selection. While this QTL effect has not been observed in other salmonids, genome editing may have potential for transferring IPNV-resistance alleles or mechanisms to other species, such as rainbow trout, the salmonid with the second largest production.Systems involving the clustered regularly interspaced short palindromic repeats (CRISPR) and its associated proteins (Cas) have become the most reliable tools for gene editing and assessment of gene function, both in cell lines and in vivo. In vitro models allow for an initial optimisation of the genome editing technique, determination of the target locus as well as a preliminary assessment of possible off target effects, thus providing useful groundwork to apply genome editing in vivo at a later stage. However, CRISPR editing has not yet been reported in rainbow trout cell lines. Here we developed and optimised an efficient genome editing method for rainbow trout cells (RTG-2, rainbow trout gonad), and subsequently used this system to perturb candidate genes for the IPNV resistance major QTL found in Atlantic salmon, measuring their impact on IPNV infection. To develop an efficient genome editing technique in this cell line, electroporation conditions were optimised for the delivery of ribonucleoprotein complexes. The editing efficiencies of two different Cas proteins (spCas9 and AsCas12a) in RTG-2 were measured, exhibiting repeatable editing efficiencies of > 90 %. This is the first successful application of CRISPR editing in a rainbow trout cell culture and ...